2020
DOI: 10.1186/s12884-020-02903-1
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiologic characteristics and associated risk factors of preterm birth from 2004 to 2013 in Taiwan

Abstract: Background: The rate of preterm birth has been increasing worldwide. Most preterm babies are at an increased risk of central nervous system impairments as well as respiratory and gastrointestinal complications. The aim of this study was to investigate the epidemiologic characteristics of and associated factors contributing to preterm birth in Taiwan. Methods: Information on obstetric antecedents and risk factors for preterm birth in pregnant women was obtained from the National Health Insurance Research (NHIR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 55 publications
(60 reference statements)
4
27
0
4
Order By: Relevance
“…In this study, the adverse fetal outcome were the main outcome variables. It was defined as the occurrence of one or more of the following fetal outcomes: LBW (delivery of a live infant whose birth weight was less than 2500 g), 37 , 38 preterm (babies born alive before 37 weeks of pregnancy are completed), 39 low Apgar score at 5 minutes (less than 7), neonatal death (death of a live birth within 28 days), 12 stillbirth (fetal death at or after 28 weeks gestation). 29 The wealth index was generated using 26 variables.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, the adverse fetal outcome were the main outcome variables. It was defined as the occurrence of one or more of the following fetal outcomes: LBW (delivery of a live infant whose birth weight was less than 2500 g), 37 , 38 preterm (babies born alive before 37 weeks of pregnancy are completed), 39 low Apgar score at 5 minutes (less than 7), neonatal death (death of a live birth within 28 days), 12 stillbirth (fetal death at or after 28 weeks gestation). 29 The wealth index was generated using 26 variables.…”
Section: Methodsmentioning
confidence: 99%
“… 9 Risk factors of early‐term deliveries were reported as socioeconomic factors, environmental factors, pregnancy‐related complications, or medical indications; however, some of these deliveries were not medically indicated. 10 , 11 …”
Section: Introductionmentioning
confidence: 99%
“…85,86 Factors such as nulliparous women, multiple pregnancies, advanced maternal age (≥40 years), history of PTD, and maternal medical disorders have also been identified as main predictive factors for the risk of preterm babies. 87 Studies also indicated that obese women (BMI≥30kg/m 2 ) 41 ; underweight women (BMI≤18.5kg/m 2 ), 40 some ethnic minorities, vegetarians and vegans to be at risk of MN deficiencies 74 which made the women more prone to adverse pregnancy outcomes. Studies reported also that markers of maternal pre-pregnancy status like short stature, low and high BMI are linked to increased risks of PTD and SGA.…”
mentioning
confidence: 99%